2018
DOI: 10.1177/1367006918781067
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual and monolingual children’s articulation rates during nonword repetition tasks

Abstract: Aims and objectives: We know little about how the rate of speaking develops in bilingual children. The purpose of the current investigation was to explore the second language (L2) articulation rate in Spanish-English bilingual kindergarten children, and to compare the rates with those of monolingual English-speaking peers. Method/design: We performed a group-level, longitudinal study comparing articulation rates in two language groups (monolingual and bilingual). Data and analysis: Sixty-two monolingual Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…For example, they often do not reach the developmental milestones in their linguistic competence of L1 at the same pace as monolingual children or have difficulties acquiring L2, the dominant language of the society ( Paradis 2010). It is also observed that, compared to monolingual children, bilinguals often perform linguistic tasks more poorly ( Gibson, Jarmulowicz, Oller 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they often do not reach the developmental milestones in their linguistic competence of L1 at the same pace as monolingual children or have difficulties acquiring L2, the dominant language of the society ( Paradis 2010). It is also observed that, compared to monolingual children, bilinguals often perform linguistic tasks more poorly ( Gibson, Jarmulowicz, Oller 2019).…”
Section: Introductionmentioning
confidence: 99%